2016
DOI: 10.1371/journal.pone.0159923
|View full text |Cite
|
Sign up to set email alerts
|

BiCAMWI: A Genetic-Based Biclustering Algorithm for Detecting Dynamic Protein Complexes

Abstract: Considering the roles of protein complexes in many biological processes in the cell, detection of protein complexes from available protein-protein interaction (PPI) networks is a key challenge in the post genome era. Despite high dynamicity of cellular systems and dynamic interaction between proteins in a cell, most computational methods have focused on static networks which cannot represent the inherent dynamicity of protein interactions. Recently, some researchers try to exploit the dynamicity of PPI network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Lakizadeh et al integrated time series expression data and static PPI networks to extract dynamic PPI subnetwork and then detected protein complex based on these subnetworks. They concluded that this method could model the dynamicity inherent in static PPI networks [111].…”
Section: Biological Network Elucidationmentioning
confidence: 99%
“…Lakizadeh et al integrated time series expression data and static PPI networks to extract dynamic PPI subnetwork and then detected protein complex based on these subnetworks. They concluded that this method could model the dynamicity inherent in static PPI networks [111].…”
Section: Biological Network Elucidationmentioning
confidence: 99%
“…These methodologies involve the extraction of dynamic subnetworks through integrating diverse data sources and subsequently achieve dynamic protein complex identification by filtering clustering outcomes from all subnetworks. Among these methods, the BiCAMWI algorithm [5] , based on genetic algorithms, introduces a novel adaptive degree function for dual cluster evaluation. It then extracts the gene set within these dual clusters to form a subnetwork, i.e., a dynamic subnetwork.…”
Section: Introductionmentioning
confidence: 99%
“…BiCAMWI (Lakizadeh and Jalili, 2016 ) is one of the methods that uses a genetic algorithm to detect dynamic biclusters from gene expression data. For each detected bicluster, BiCAMWI makes a dynamic subnetwork of PPI and protein complexes are detected from each subnetwork separately by applying CAMWI.…”
Section: Introductionmentioning
confidence: 99%